Outcome and management in neonatal thrombocytopenia due to maternal idiopathic thrombocytopenic purpura. Issue 3 (19th June 2013) - van der, N. M.; van, A.; Walther, F. J.; Brand, A.; Lopriore, E.
<x xml:space="preserve">Abstract</x> Background and Objectives Pregnant women with Idiopathic thrombocytopenic purpura (ITP) can deliver neonates with severe thrombocytopenia. Clear evidence declaring the pathophysiological cause of this neonatal thrombocytopenia is lacking, as antiplatelet antibodies are not always detectable in maternal serum. Severe neonatal thrombocytopenia below 50 × 109/l is reported in 8–13% of the neonates from mothers with ITP and intracranial haemorrhage (ICH) in 0–2·9%. Evidence about the optimal postnatal treatment is scarce. Our objective was to evaluate the outcome and management in neonates with passive ITP. Materials and Methods All neonates from mothers with ITP born between 1980 and 2011 were included. Platelet counts during the first 10 days, presence of ICH and postnatal treatment were recorded. Maternal characteristics were analysed as possible risk factors for severe neonatal thrombocytopenia. Results Sixty‐seven neonates were included. Severe thrombocytopenia (<50 × 109/l) occurred in 20/67 (29·9%) neonates. In three neonates, platelet count rose spontaneously, 18 neonates were treated (one with persistent moderate thrombocytopenia) with the following: platelet transfusions (3), prednisone (2), intravenous immunoglobulin (IVIG) (1), platelet transfusions and IVIG (11), platelet transfusion and prednisone (1). Recurrence of low platelet counts after transfusions was commonly seen. Risk factors for severe neonatal thrombocytopenia were a previous sibling with severe thrombocytopenia and low maternal platelet nadir during pregnancy. Conclusion In this cohort, severe neonatal thrombocytopenia occurs more frequently than previously reported. To maintain a platelet count above 50 × 109/l, often multiple transfusions and IVIG are required. Multiple transfusions may be avoided by starting IVIG, when platelet count falls below 50 × 109/l after the first platelet transfusion.